Hybrid semiconductor quantum dot / quantum well & metal nanoparticle structures - Murphy, Graham P. (Trinity College (Dublin, Ireland). School of Physics, 2016)
Non-radiative energy transfer is an energy transfer mechanism based on dipoledipole interactions. It has come to the fore in biomedical imaging and sensing, as well as light emitting and harvesting applications. Utilising non-radiative energy transfer in hybrid semiconductor quantum dot and quantum well systems is just one avenue of exploration for improving the efficiency of said light emitting/ harvesting devices. Combining these hybrid systems with metal nanoparticles that display surface plasmon resonances can improve the efficiency, rate, and effective distance of the non-radiative energy transfer. Thus, in this work the surface plasmon-mediated non-radiative energy transfer interaction between pairs of quantum dots, and between quantum dots and quantum wells is investigated both to increase fundamental understanding of the system and with a view towards viable device applications ...
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2016